Analisis Dampak Keterbatasan Persediaan Bahan Pangan di Pasar MMTC : Perspektif Konsumen - Mita Nalsalisa Br Barus; Esra Silaban; Shika Andari; Fadilla Khoiri; Angelo Arevalo Simanullang (Departement of Mathematics Education, 2024)
This research aims to analyze the impact of limited food supplies in the MMTC market. Pasar Raya Medan Mega Trade Center (MMTC) is a market located on Jalan Memori Baru, Percut Sei Tuan District, Deli Serdang. This market looks increasingly busy, especially at night from midnight. 11.00 until morning. The hustle and bustle of loading and unloading of goods from various regions with their respective buyers. Pasar Raya Medan Mega Trade Center (MMTC) is one of the largest traditional markets in Medan, North Sumatra, Indonesia. This market is famous for its various kinds of fresh products, including foodstuffs. However, in recent years, there has been increasing concern about limited food supplies in this market. This has led to negative impacts on consumers, such as higher prices, fewer choices and lower quality.